Peningkatan Kesadaran Fertilitas bagi Tenaga Kesehatan di Puskesmas Bakunase dan Puskesmas Sikumana, Kupang, NTT, Indonesia - Andriana Kumala Dewi1; Cindy Yusliani; Caitlyn Natasha Horyono; Kiswa Anggreany (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Infertility, according to the World Health Organization (WHO), affects approximately 8-12% of couples of reproductive age worldwide. In Indonesia, its prevalence ranges from 10-15%, meaning about 4-6 million couples require treatment to conceive. The incidence of infertility is influenced by various factors, including access to and the quality of healthcare services. Therefore, healthcare providers’ knowledge and awareness of infertility play a crucial role in its management, leading to early detection and appropriate referrals to advanced healthcare facilities. Given the limited access to information and healthcare services in remote areas, educating and promoting early detection of infertility by healthcare providers is essential to improving healthcare quality in those regions. This community service activity aims to enhance healthcare workers' understanding of diagnosing infertility, ensuring that patients are promptly referred for further treatment. The activity took place on Friday, November 15, 2024, via Zoom Meeting, in collaboration with an experienced OB/GYN doctor in Kupang. A total of 27 participants attended, consisting of 20 people from Bakunase Health Center and 7 people from Sikumana Health Center.